Proceedings of the International Conference on Research and Academic Community Services (ICRACOS 2019) 2020
DOI: 10.2991/icracos-19.2020.24
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception Toward the Implementation of Project Based Learning for EFL Vocational High School.

Abstract: This study focused on the students' perceptions toward the implementation of Project Based Learning in learning English as a Foreign Language that was conducted in one public of vocational high school in Surabaya Indonesia. The research was mixed method that used quantitative and qualitative data. The instruments were questionnaire, observation sheet and interview to examine the students' and teacher's perception. The participants included one teacher and 45 students aged between 15 and 16 years old. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
2
Order By: Relevance
“…Because the subjects of this research were only 59 people, the researchers also carried out a semi-structured interview approach to obtain more in-depth and accurate information. Researchers used six questions adapted from Susanti et al, (2020) for semi-structured interview sessions as a follow-up to find out students' points of view on the topic. This is in line with the research objectives that researchers have conducted.…”
Section: Research Methodology Research Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the subjects of this research were only 59 people, the researchers also carried out a semi-structured interview approach to obtain more in-depth and accurate information. Researchers used six questions adapted from Susanti et al, (2020) for semi-structured interview sessions as a follow-up to find out students' points of view on the topic. This is in line with the research objectives that researchers have conducted.…”
Section: Research Methodology Research Designmentioning
confidence: 99%
“…In recent years there has been research on project-based learning. Students' perceptions of the implementation of project-based learning in vocational high schools (Susanti et al, 2020;Sofiya Septiana et al, 2023). Development of teaching modules for project-based learning methods (Adiningtyas & Rahayu, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Sejalan dengan Listiani et al (2021) bahwa komponen yang harus diperhatikan dalam penyusunan RPP, yakni identitas sekolah; identitas mata pelajaran/ tema, subtema; kelas/semester; materi pokok; alokasi waktu; tujuan pembelajaran; KD dan indicator; dan penilaian hasil belajar. Melalui media pula, pembelajaran dapat lebih bermakna bagi siswa karena dengan menggunakan media maka tidak sekadar menggunakan symbol verbal tapi juga menggunakan symbol lain seperti warna, bentuk, bahkan mungkin gerak (Susanti et al, 2020) Berdasarkan tabel di atas dapat diketahui bahwa hasil model pelaksanaan pembelajaran tematik terpadu berbasis proyek di SD Perbatasan diperoleh persentase rata-rata sebesar 84,4%, SD Pinggiran sebesar 71,4 %, dan SD Perkotaan sebesar 88,6%. dan Kategori untuk pelaksanaan pembelajaran oleh SD Perbatasan dan Perkotaan terkualifikasi baik, sedangkan SD Pinggiran terkualifikasi cukup baik.…”
Section: Hasil Dan Pembahasanunclassified
“…Di SD Perbatasan dan Perkotaan, semua siswa terlibat dalam pemanfaatan media yakni dengan guru memberikan kesematan pada maisngmasing siswa namun di SD Pinggiran tidak semua siswa ikut andil dalam pemanfaatan media. Walau ada beberapa kekurangan namun hal tersebut sejalan dengan pendapat Susanti et al (2020) bahwa dengan menggunakan media, pembelajaran dapat lebih bermakna karena siswa ikut serta dalam pemnafaatannya.…”
Section: Hasil Dan Pembahasanunclassified
“…The result also found that students though this method was appropriate conducted to the class. While (Susanti, et al 2020) 2020) stated that perception is an important psychological human aspect in responding to the presence of various aspects and symptoms around them. This is the process of people to respond the social phenomenon that happens around.…”
mentioning
confidence: 99%